1999
DOI: 10.1128/jb.181.11.3433-3437.1999
|View full text |Cite
|
Sign up to set email alerts
|

Growth Phase-Regulated Induction of Salmonella -Induced Macrophage Apoptosis Correlates with Transient Expression of SPI-1 Genes

Abstract: Invasive Salmonella has been reported to induce apoptosis in a fraction of infected macrophages within 2 to 14 h from the time of infection by a mechanism involving the type III secretion machinery encoded by the Salmonella pathogenicity island 1 (SPI-1). Here, we show that bacteria in the transition from logarithmic to stationary phase cause 90% of the macrophages to undergo phagocytosis-independent, caspase-mediated apoptosis within 30 to 60 min of infection. The ability of Salmonella to induce this rapid ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(76 citation statements)
references
References 37 publications
1
74
0
1
Order By: Relevance
“…Bacterial infection assays were performed as previously described (41). Bacteria grown to stationary phase were used for all infection assays to limit SPI-1-dependent cell death of S. Typhimurium-infected macrophages (42,43). In brief, bacteria were grown overnight in Luria-Bertani (LB) medium, washed twice, resuspended in antibiotic-free cell culture medium and then used to infect cultured human macrophages at the desired multiplicity of infection (MOI).…”
Section: Bacterial Infection Assaysmentioning
confidence: 99%
“…Bacterial infection assays were performed as previously described (41). Bacteria grown to stationary phase were used for all infection assays to limit SPI-1-dependent cell death of S. Typhimurium-infected macrophages (42,43). In brief, bacteria were grown overnight in Luria-Bertani (LB) medium, washed twice, resuspended in antibiotic-free cell culture medium and then used to infect cultured human macrophages at the desired multiplicity of infection (MOI).…”
Section: Bacterial Infection Assaysmentioning
confidence: 99%
“…These results are consistent with previous observations relative to the involvement of the TTSS-1 in the apoptosis induced by Salmonella on host cells. 54,55 DInvC Salmonella fails to enter non-phagocytic cells but shows increased DCs invasion…”
Section: Generation Of a Salmonella Dinvc Mutant Strainmentioning
confidence: 99%
“…Regulation of several other virulence genes seems to be even more complex. For example, SPI1 invasion genes and spv genes are thought to be regulated by a host of environmental conditions and regulatory pathways (Table 1) (Guiney et al, 1995;Bajaj et al, 1996;Slauch et al, 1997;Lundberg et al, 1999) making it difficult to know which signals and regulators modulate the genes at any given site in vivo.…”
Section: Misleading Clues?mentioning
confidence: 99%
“…1B). Lundberg et al (1999) reported that they observed transient activation of invF under specific conditions in vitro even when hilA was disrupted. Still, no one has reported a condition in which wild-type S. typhimurium represses hilA expression while simultaneously activating expression of invF and invF-dependent genes through HilC or HilD.…”
Section: Models For Invasion Gene Regulation In Vitromentioning
confidence: 99%